2020
DOI: 10.22146/jlo.57406
|View full text |Cite
|
Sign up to set email alerts
|

Millennial Leaders’ Display of Generational Cohort Stereotypes: A Qualitative Research Approach

Abstract: This paper investigates how Millennial leaders perceive themselves in their leadership role and whether generational cohort stereotypes prevail with ascending hierarchy levels. There is a lack of research, which applies generational cohort stereotypes to Millennials in a leadership context. This limits our understanding of this generational cohort and how its members can benefit organizations in their role as leaders. Millennials in leadership positions are a new and underresearched phenomenon. Therefore, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Based on this perception, it is concluded that there could be other various classifications of the workforce, not only based on the cohort year range, which could be changed as time goes on regarding the context. as the USA (Anderson et al, 2017;Archibald, 2013;Bennett, 2020;Cohen, 2019;Ferri-Reed, 2014;Ferris et al, 2018a;Kim, 2018;Kosterlitz & Lewis, 2017;Scott, 2017;Stewart et al, 2017) Germany (Grotkamp et al, 2020;Percy-Smith et al, 2019;Rudolph et al, 2018) and other Europe countries: UK (Baum, 2020;Geerts et al, 2020;Thompson & Gregory, 2012),…”
Section: Assortment Of Papers Based On Contextmentioning
confidence: 99%
“…Based on this perception, it is concluded that there could be other various classifications of the workforce, not only based on the cohort year range, which could be changed as time goes on regarding the context. as the USA (Anderson et al, 2017;Archibald, 2013;Bennett, 2020;Cohen, 2019;Ferri-Reed, 2014;Ferris et al, 2018a;Kim, 2018;Kosterlitz & Lewis, 2017;Scott, 2017;Stewart et al, 2017) Germany (Grotkamp et al, 2020;Percy-Smith et al, 2019;Rudolph et al, 2018) and other Europe countries: UK (Baum, 2020;Geerts et al, 2020;Thompson & Gregory, 2012),…”
Section: Assortment Of Papers Based On Contextmentioning
confidence: 99%
“…Through their study, Ng and Perry (2016) note the need for a comprehensive review, understanding and interpretation of the millennials' professional career explorations and expectations. These components also help managers respond to the millennials' personal priorities, formulate unique career opportunities, and create productive work settings with a stronger propensity to attract, engage and retain millennial workers (Grotkamp et al. , 2020; McNally, 2017; PriceWaterhouseCoopers, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through their study, Ng and Perry (2016) note the Managerial insights on millennials need for a comprehensive review, understanding and interpretation of the millennials' professional career explorations and expectations. These components also help managers respond to the millennials' personal priorities, formulate unique career opportunities, and create productive work settings with a stronger propensity to attract, engage and retain millennial workers (Grotkamp et al, 2020;McNally, 2017;PriceWaterhouseCoopers, 2016). Acknowledging and responding to the differences in generations in the workplace may enhance the perspectives of managers and their understandings of millennial workers and how to develop them to meet organizational objectives (Hoffman, 2018;Volini et al, 2020;Wood, 2019).…”
Section: Introductionmentioning
confidence: 99%